The perceptions of Speech-Language Pathology and Audiology students towards online learning during the COVID-19 pandemic: Considerations for the future professoriate - Govender, S.; Kyarkanaye, T.; Eslick, C. (South African Journal of Higher Education, 2024)
The widespread effects of the COVID-19 pandemic in March 2020 led to the suspension of various activities, including education. Institutions responded by shifting to online learning, albeit facing challenges. Student perceptions on online learning are valuable for academic leadership in shaping pedagogies and policies. This study examines Speech-Language Pathology and Audiology students’ perceptions (n=43) of online classes during the pandemic. Findings from a descriptive online survey with convenience sampling show that students favoured advantages such as recorded lectures, access to online materials, and self-paced study. However, they highlighted drawbacks like technical issues, limited patient interaction, and reduced engagement with lecturers. Online learning was regarded as effective for enhancing knowledge than for developing clinical skills or social competencies, whilst face-to-face teaching was seen as more effective for fostering clinical skills and social competence compared to online learning. While online learning was initially seen as a response to the pandemic, its formalization as part of a blended education approach in South African universities should align with global trends.